Malaysian Natural Rubber Market Model - Yusof, Mohammed (1988)
This study is an attempt to formulate a simultaneous equations model of the Malaysian natural rubber market. The regression results suggest that the model is quite satisfactory in terms of correct signs, high R 2, and significance of variables concerned. A simulation exercise was done to ascertain the adequacy of the model in tracking the actual values. It was found that, in general, the model has the ability to trace, at least, the directions of the movements of certain selected endogenous variables. The model developed here could be used to forecast the effect of a change in an endogenous variable, such as export duty, exchange rates, or recession on endogenous variables.